(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
The aim of the study is to determine and record mangrove species biodiversity and structure at Kudat Mainland and Banggi Island. The sampling plots with a size of 100 m x 10 m and four (4) replication was established to measure the species diversity by using Shannon-Wiener Index (H’), Shannon Evenness Index (E) and Simpson’s Diversity Index (D). From the results, a total of 10 mangrove species were recorded from both study areas. There are eight (8) species at Kudat Mainland and six (6) species at Banggi Island. The diversity indexes give the value of H’, E and D with a similar value at both study areas. At Kudat Mainland, H’ = 1.51, E = 0.73 and D = 0.29 while at Banggi Island H’ = 1.50, E = 0.84 and D = 0.29. The results of these values show the value of diversity in both areas is less diverse. The findings show the representation of mangrove species in both areas are may be affected by the water salinity, tidal inundations, soil conditions and propagules size. While the dependency of local people on mangrove’s wood and tree’s age will be affected the distribution of mangrove diameter. Meanwhile, the current of winds and types of species represented in a plot assume affected the results of distributions of mangrove height. Represented of species less than 8 species assume affected the values of mangrove species diversity. In conclusion, the mangrove species at Kudat district can be determined and recorded and the diversity of mangrove species in both areas is less diverse.